Downstream flat plate as the flow-induced vibration enhancer for energy harvesting - Maruai, N. M. (SAGE Publications Inc., 2017)
The prospect of harvesting energy from flow-induced vibration using an elastic square cylinder with a detached flat plate is experimentally investigated. The feasibility of flow-induced vibration to supply an adequate base excitation for micro-scale electrical power generation is assessed through a series of wind tunnel tests. The current test model of a single square cylinder is verified through a comparable pattern of vibration amplitude response with previous experimental study and two-dimensional numerical simulations based on the unsteady Reynolds averaged Navier–Stokes (URANS). In addition, a downstream flat plate is included in the wake of the square cylinder to study the effects of wake interference upon flow-induced vibration. A downstream flat plate is introduced as the passive vibration control to enhance the magnitude of flow-induced vibration and simultaneously increases the prospect of harvesting energy from the airflow. The study is conducted by varying the gap separation between the square cylinder and flat plate for 0.1≤ G/D ≤3. The highest peak amplitude is observed for the gap G/D = 1.2 with yrms/D = 0.46 at UR = 17, which is expected to harvest ten times more energy than the single square cylinder. The high amplitude vibration response is sustained within a relatively broader range of lock-in synchronization. Meanwhile, for G/D = 2 the vibration is suppressed, which leads to a lower magnitude of harvested energy. Contrarily, the amplitude response pattern for G/D = 3 is in agreement with the single square cylinder. Hence, the flat plate has no significance to the wake interference of the square cylinder when the gap separation is beyond 3D.